PENGEMBANGAN PERANGKAT PEMBELAJARAN TEAM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Monoarfa, Indriyani; Arbie, Asri; Nuayi, Wahidin (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2023)
This researc is the devolopment of learning tools with the aim of producing quality learning tools. This learnng tools was development using the Borg and Gall develompment model which was modified by Sukmadinata and friends, consisting of 3 stages of development. The learning device is said to be valid and used with a slight revision based on the average validation result with a value of 3.0-3.5. Learning tools are said to be practical based on the average percentage of learning outcomes for 2 meetings, which is 93.75%, and teacher and student response questionnaires related to the use of online learning tools get a positive response. The effectiveness of learning tools is seen in increasing student learning outcomes consisting of the cognitive domain at the first meeting until the second meeting, the N-Gain iRAT 0.51 and 0.46 are obtained with the criteria of "moderate", in the tRAT the N-Gain is 0.53 and 0.5 with "medium" criteria. The attitude domain with an average percentage of 80.07%, and the skill domain percentage of 81.85%, and the results of observing student activities in 2 meetings of 80.10% with good criteria